ALAT PEMBAYARAN MENGGUNAKAN KARTU DAN PERMINTAAN UANG KARTAL DI INDONESIA - Tiara Nirmala (Universitas Negeri Padang, 2012)
This study aimed to analyze the effect to using a payment card on the demand for money, especially in Indonesian currency in the long and short term. The data used in this study is a secondary data in the form of time series data months of the year 2008:1 until 2010:12. The variables used are real currency demand as the dependent variable, while the real GDP, interest rate, interest parity condition, and payment transactions using cards as independent variables. The method of analysis used in this study is the Engle-Granger Cointegration Test and Error Correction Model (ECM). The results of the assessment for Indonesia in the short term and long term, means of payment using the card have a positive influence on the demand for currency. Thus the increase in payment card has not been able to reduce the demand for currency.